PERTANGGUNGJAWABAN HUKUM TERHADAP BANK DAN DEBITUR PENERIMA FASILITAS KREDIT BANK YANG TIDAK BERDASARKAN PRINSIP KEHATI-HATIAN (ANALISIS PUTUSAN NO:2767/PID.B/2020/PN.MDN) - Adyaksa, Vicky Geraldo; Simatupang, Bachtiar (JURNAL DOKTRIN REVIEW, 2023)
Banks are companies that operate in the financial sector because they are always related to finance. Law No. 10 of 1998, explains that banks are business entities that collect funds from the public in the form of savings and distribute them to the public in the form of credit or other forms. The problem in this research is to analyze Providing Credit by Banks and Debtors to PT. Bank Tabungan Negara (BTN) Medan Branch where there were problems with the Defendant as Director of PT. Krisna Agung Yudha, who is none other than a debtor from the Bank, has handed over the original 93 SHGB to PT. State Savings Bank Medan branch to process the installation of the HGB Certificate Rights, namely 35 HGB Certificates which should be used as collateral at Bank BTN Medan Branch from the control of a Notary through an employee from the Notary's Office, that the defendant in taking the 35 HGB certificates did not have prior permission from Bank Tabungan Negara (BTN) Medan Branch. The research was conducted using normative juridical research. Based on the results of the research, it was found that there was an error in giving credit to the Debtor (Customer) where the Collateral that was the Guarantee for providing the Credit was still in the name of another person (Not Yet Changed Name).